Impact of moderate alcohol consumption on brain iron and cognition: observational and genetic analyses - Topiwala, A; Wang, C; Ebmeier, KP; Burgess, S; Bell, S; Levey, DF; Zhou, H; Mccracken, C; Roca-Fernandez, A; Petersen, S; Raman, B; Husain, M; et al. (2022)
Brain iron deposition has been linked to several neurodegenerative conditions and reported in alcohol dependence. Whether iron accumulation occurs in moderate drinkers is unknown. Our objectives were to investigate causal relationships between alcohol consumption and brain iron levels and to examine whether higher brain iron represents a potential pathway to alcohol-related cognitive deficits.